2013
DOI: 10.1016/j.ultsonch.2012.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Silica chloride catalyzed efficient route to novel 1-amidoalkyl-2-naphthylamines under sonic condition in water

Abstract: a b s t r a c tA one-pot three-component condensation of an aldehyde, 2-naphthylamine, and acetamide has been achieved by sonication at 35 kHz. The reaction is catalysed by silica chloride in aqueous medium. This protocol afforded corresponding 1-amidoalkyl-2-naphthylamines in shorter reaction durations, and in high yields. The method involves simple work-up procedure, and avoids use of hazardous reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…_________________________________________________________________________________________________________________________ Available on line at www.shd.org.rs/JSCS/ condensations of aldehydes (1), acetamide (94) and 2-naphthylamine (95) using silica chloride as a catalyst in aqueous medium at ambient temperature (Scheme 39). 174 Use of organic solvents, such as CH 3 CN, CHCl 3 , DCM, DCE and EtOH, gave inferior results in terms of both reaction times and yields. It was also observed that ultrasonic irradiation has a distinct effect on the rate of the reaction.…”
Section: Synthesis Of 1-(amidoalkyl)-2-naphthylaminesmentioning
confidence: 99%
“…_________________________________________________________________________________________________________________________ Available on line at www.shd.org.rs/JSCS/ condensations of aldehydes (1), acetamide (94) and 2-naphthylamine (95) using silica chloride as a catalyst in aqueous medium at ambient temperature (Scheme 39). 174 Use of organic solvents, such as CH 3 CN, CHCl 3 , DCM, DCE and EtOH, gave inferior results in terms of both reaction times and yields. It was also observed that ultrasonic irradiation has a distinct effect on the rate of the reaction.…”
Section: Synthesis Of 1-(amidoalkyl)-2-naphthylaminesmentioning
confidence: 99%
“…Over recent decades multicomponent reactions (MCRs) have gained ever increasing attention from the synthetic community, because they act as an exceptionally efficient and powerful tool for one‐pot transformation of simple and readily available starting materials into relatively complex molecules that represent valuable intermediates in the synthesis of various natural products and pharmaceuticals In particular, the Mannich‐type three‐component condensation reaction of diverse electron‐rich arenes and heteroarenes with aldehydes and various nitrogen nucleophiles has emerged as a versatile and straightforward approach to C–C bond formation, which is of current importance in modern organic synthesis. Thus far, transformations of this type that feature aromatic aldehydes as electrophilic components have been extensively applied to functionalization of phenols, α‐naphthols, β‐naphthols (Betti reaction), hydroxyquinolines[3a], and other heteroannelated phenols, some electron‐rich benzenes, naphthylamines, indoles, 7‐azaindoles and indolizines, whereas examples of employing other heterocycles, particularly, pyrrole, thiophene and furan derivatives, are scarcely encountered in literature. Jaratjaroonphong and co‐workers reported a versatile iodine‐catalyzed carbamoalkylation procedure that used benzyl‐ and tert ‐butyl carbamates with a variety of aldehydes, which was successfully applied to 2‐alkylfurans and 2‐methylthiophene.…”
Section: Introductionmentioning
confidence: 99%
“…In addition of advantages, such as shorter reaction times, milder reaction conditions, higher yields, improved selectivity and clean reactions in comparison to classical methods, [16][17][18] in this green technique the reaction is carried out at a lower external temperature relative to the usual thermal methods; the possibility of the occurrence of undesired reactions is reduced, and as a result of cleaner reaction work-up is easier. 19 In spite of the signicant useful attributes of multicomponent reactions (MCRs) for modern organic chemistry and their suitability for building up large compound libraries, these reactions were of limited interest in the past y years. However, in the last decade, with the introduction of highthrough put biological screening, the importance of MCRs for drug discovery has been recognized, and considerable efforts from both academic and industrial researchers have been focused, especially on the design and development of multicomponent procedures for the generation of libraries of heterocyclic compounds.…”
Section: Introductionmentioning
confidence: 99%